Answers

2014-08-25T14:39:49+08:00
Given the roots:
for example you are given 2 and 3 as the roots of your quadratic equation.

that means x=2 and x=3

transpose the constant to the other side

(x-2)  and (x-3)

remember when you are transposing, you will change the sign to it's opposite.

after that, multiply (x-2)(x-3)

it will result to x^2-5x+6

if the given root is a fraction. cross multiply

x= \frac{1}{2}

2x=1
(2x-1)

given sum (s) and product (p)

just use the equation below and substitute

x^2-sx+p=0

example:

write a quadratic equation knowing the the sum of its roots is 8 and its product is 16.

then s=8 and p=16

 x^{2} -8x+16=0
1 5 1
2014-08-25T16:42:11+08:00
Here's the formula x^2-sumx+product
0